Discovery and preclinical profile of LX-039, a novel indole-based oral selective estrogen receptor degrader (SERD). (15th June 2022) - Lu, Jianyu; Chan, Chi-chung; Sun, Deheng; Hu, Guoping; He, Huijun; Li, Jian; Dong, Jiaqiang; Liu, Kai; Shen, Liang; Hu, Lihong; Gu, Qingyang; Chen, Shuhui; et al.
Graphical abstract: Abstract: We previously described the discovery of a novel indole series compounds as oral SERD for ER positive breast cancer treatment. Further SAR exploration focusing on substitutions on indole moiety of compound 12 led to the discovery of a clinical candidate LX-039. We report herein its profound anti-tumor activity, desirable ER antagonistic characteristics combined with favorable pharmacokinetic and preliminary safety properties. LX-039 is currently in clinical trial (NCT04097756).